2017
DOI: 10.4067/s0718-19572017000300011
|View full text |Cite
|
Sign up to set email alerts
|

Pilot-scale production of the rotifer Brachionus sp. under different culture systems

Abstract: Resumen.-Pequeños Brachionus sp. (130-230 µm) en 2011-2012 y superpequeños Brachionus sp. (110-140 µm) en 2013-2014, se cultivaron en un sistema por lotes (ciclos de 3 o 4 días) y en sistemas semi-continuos. Para la alimentación de rotíferos se usaron microalga concentrada (Nannochloropsis sp.), dosificada continuamente con una bomba peristáltica. Las condiciones del cultivo fueron provistas con aire, oxígeno e hidroximetanosulfonato de sodio. La producción total promedio por día fue 552, 602 y 459 millones de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…(2003) and Rojo‐Cebreros et al. (2017). The un‐ionized form of ammonia is a major threat in high‐density rotifer production, but it was not observed above 1.16 mg/L throughout the culture period in our study.…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…(2003) and Rojo‐Cebreros et al. (2017). The un‐ionized form of ammonia is a major threat in high‐density rotifer production, but it was not observed above 1.16 mg/L throughout the culture period in our study.…”
Section: Resultsmentioning
confidence: 97%
“…Likewise, Sananurak et al (2009) suggested that the dissolved oxygen level should be kept above 3.0 mg/L. On the other hand, Rojo-Cebreros et al (2017) maintained the dissolved oxygen level at 8.6-8.7 mg/L by using respironics for high-density culture. Total hardness and alkalinity have not shown any effect on rotifer production while pH was maintained between 7.4 and 8.8, as suggested by Suantika et al (2003) and Rojo-Cebreros et al (2017).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations